Two decades of seawater acidification experiments on tropical scleractinian corals: Overview, meta-analysis and perspectives. (May 2022) - Godefroid, Mathilde; Dupont, Sam; Metian, Marc; Hédouin, Laetitia
Abstract: Ocean acidification has emerged as a major concern in the last fifteen years and studies on the impacts of seawater acidification on marine organisms have multiplied accordingly. This review aimed at synthesizing the literature on the effects of seawater acidification on tropical scleractinians under laboratory-controlled conditions. We identified 141 articles (published between 1999 and 2021) and separated endpoints into 22 biological categories to identify global trends for mitigation and gaps in knowledge and research priorities for future investigators. The relative number of affected endpoints increased with pH intensity (particularly for endpoints associated to calcification and reproduction). When exposed to pH 7.6–7.8 (compared to higher pH), 49% of endpoints were affected. The diversity in experimental designs prevented deciphering the modulating role of coral life stages, genera or duration of exposure. Finally, important bias in research efforts included most experiments on adult corals (68.5%), in 27 out of 150 (18%) coral ecoregions and exclusively from shallow-waters. Highlights: Seawater acidification experiments on tropical scleractinians are relatively recent. Seawater acidification mainly affects calcification and reproduction capacities. Knowledge is biased with a majority of work on adult and shallow-water corals. Geographical bias: acidification experiments performed in only 18% of coral ecoregions. We recommend a list of actions and priorities for future research in this field.